2017
DOI: 10.1177/2050312117712886
|View full text |Cite
|
Sign up to set email alerts
|

Markers of arterial stiffness in a sample of Lebanese subjects with Grade I essential hypertension

Abstract: Objectives:Arterial stiffness is becoming a major global condition associated with an increased risk of cardiovascular problems and death. Several markers have been linked to arterial stiffness.Methods:To determine and evaluate these relations, anthropometric parameters (weight, height, and pulse rate), biochemical profile, and central and peripheral indices of arterial function were measured in 114 Lebanese subjects with Grade I essential hypertension.Results:Age was associated with a higher pulse wave veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Obesity, which has reached an epidemic level owing to economic development in China, often coexists with MetS [9]. While the correlation between obesity and baPWV has not exhibited consistent results [10,11]. Currently, a subset of obese individuals without MetS, identi ed as metabolically healthy obese (MHO), attracted extensive attention due to the inconsistency on cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, which has reached an epidemic level owing to economic development in China, often coexists with MetS [9]. While the correlation between obesity and baPWV has not exhibited consistent results [10,11]. Currently, a subset of obese individuals without MetS, identi ed as metabolically healthy obese (MHO), attracted extensive attention due to the inconsistency on cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…BMI is one of the main measures for general obesity, and is commonly used in clinical assessment and screenings. However, researches on the association between BMI and baPWV among hypertensive patients have not shown consistent results; studies have reported an insignificant relationship [9], positive relationship [10], or negative relationship [11,12]. Possible reasons for these conflicts might be study limitations of small sample size or different origins of the study population.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Huang et al [29] and Liu et al [18] found that there was a negative relationship between BMI and baPWV among male hypertension participants. On the contrary, previous studies showed that a higher BMI was associated with increased PWV in Grade I essential hypertension [15] or obese and non-obese hypertensive patients [17]. Different origins of the study participants might contribute to the study differences.…”
Section: Discussionmentioning
confidence: 81%
“…The Liu et al [18] study was based on 699 male hypertensive patients who were hospitalization or had other complications. The Samir et al [15] study was based on 114 patients with Grade I essential hypertension who were civil servants. The Huang et al [29] study enrolled 10 1510 participants, a coal occupation group in labor-intensive enterprise, from 11 hospitals in the Kailuan community, which is most similar to our rural hypertensive crowd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation